Analisis Faktor Yang Berhubungan Dengan penerapan Kawasan Tanpa Rokok(KTR) Di Wilayah Puskesmas Sei Agul Kota Medan Tahun 2019 - Nurlina Fari Harahap (Jurnal Kajian Kesehatan Masyarakat, 2020)
Smoking is one of the unhealthy lifestyles. Every time you inhale cigarette smoke, whether intentionally or unintentionally, it also means sucking in thousands of poisons. Following the impact of smoking on human health and the environment, the Medan city government made a regional regulation (PERDA) No. 3/2014, 30 January2014 regarding without smoking areas in the Puskesmas area. This study aims to analyze the factors associated with the expansion of without smoking areas (KTR) in Puskesmas Sei Agul in 2019. The type of research used in this research is mixed methods with a total sample of 60 people with quota sampling technique. Data collection using a questionnaire. Data analysis using univariate analysis and bivariate analysis using chi-square test at 95% confidence level, α=5%. The category of knowledge about Regions Without Regions is not good at 63.3%, the category of no-smoking signs is not available at 70.0%, the category of without smoke area socialization in the category does not exist at 66.7%, the category of support of the Head of Puskesmas in the category does not amount to 88.3%, the category of application of sanctions does not exist by 90.0%, the category of application of areas without cigarettes is not good at 65.0%. The results of the analysis obtained knowledge (p = 0, 026), socialization of areas without smoking by health workers ( p = 0, 04), the support of the Head of the Health Center (p = 0, 10) has an effect on the implementation of a without smoke area in the Puskesmas Sei Agul in 2019. It is expected that the Puskesmas provides media outreach in the form of video or loudspeakers related to the regulation of without smoke areas.